Composto de lodo de esgoto biotransformado como fonte de nutrientes no cultivo de Philodendron “Pink Princess” - Alves, Ana Carolina da Cruz (Universidade Federal de São Carlos, 2025)
In a scenario of increasing demand for sustainable solutions, mainly due to Brazil’s high dependence on imported fertilizers, its vulnerability to economic and geopolitical crises, and the use of finite natural resources in fertilizer production, alternative sources for nutrient recycling, such as sewage sludge, have gained prominence. After detoxification processes like bioremediation, sewage sludge can be transformed into a biotransformed compost, enabling its use as a fertilizer. Under this perspective, the present study evaluated the performance of biotransformed sewage sludge compost as an alternative nutrient source to mineral fertilization in the cultivation of Philodendron ‘Pink Princess’. The experiment was conducted in a completely randomized design with six treatments and 12 replications. The treatments were for-mulated based on the maximum dose of 3.0 g L⁻¹ of the slow-release mineral fertilizer Ba-sacote®. To determine the potential of the compost as a nutrient source (P), calculations con-sidered the P₂O₅ percentages in each source (mineral fertilizer: 8% and sludge compost: 5.9%, with sludge accounting for 20% of the compost). The evaluated treatments were: fertilization with 100% compost; 20% Basacote® and 80% compost; 40% Basacote® and 60% compost; 60% Basacote® and 40% compost; 80% Basacote® and 20% compost; and 100% Basacote® (control). Data were subjected to Tukey’s test at a 5% significance level. According to the re-sults, the treatment with 40% Basacote® and 60% compost resulted in the highest means for plant height (22.4 cm) and largest leaf length (13.2 cm). Regarding chlorophyll a, b, and total contents, treatments with 100% and 80% compost showed the lowest values, whereas treat-ments with 40% Basacote® and 60% compost, as well as 100% Basacote®, presented the best results. For phenol and total protein analyses, no significant differences were observed among treatments. The enzymes Glutathione S-transferase (GST) and Phenylalanine AmmoniaLyase (PAL) had higher means in the 100% compost treatment, indicating increased anti-oxidant enzyme activity. This suggests that plants activated antioxidant mechanisms to miti-gate the effects of reactive compounds associated with the biotransformed sludge compost. Additionally, nitrogen deficiency and the high aluminum concentration in this treatment contributed to the high enzymatic activity. Regarding stomatal conductance, the 100% compost treat-ment showed a significant reduction, impairing stomatal opening and gas exchange. Similarly, the efficiency of photosystem II was affected, reducing photosynthetic capacity, possibly due to the low nitrogen (N) content in plants subjected to this treatment. However, partial replace-ment, with up to 60% of the mineral fertilizer dose substituted by the biotransformed sewage sludge compost, showed promising results. In this sense, it is concluded that although total replacement of mineral fertilizer with the compost is not viable—most likely due to its lower N content—partial replacement presented positive results for Philodendron ‘Pink Princess’ cultivation. This approach emerges as a viable solution for reducing urban waste, promoting the replacement of mineral fertilizer sources, and fostering a more sustainable and self-sufficient agriculture.
Biotransformed sewage sludge fertilizer as a source of nutrientes in the cultivation of Philodendron “Pink Princess”
Keywords: Fertilizante mineral; Tratamento de efluentes urbanos; Biorremediação; Casca de arroz; Pleurotus ostreatus; Philodendron Pink Princess.; Mineral fertilizer; Urban wastewater treatment; Bioremediation; Rice husk; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL